1978
DOI: 10.3109/08820137809025473
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoctye Cytotoxicity in the X-Irradiation Induced Rat Small Bowel Adenocarcinoma. II. Presence of Cytotoxic Lymphocytes in Irradiated Animals

Abstract: Cytotoxic peripheral blood lymphoid cells were demonstrated in both Holtzman and Lewis Brown-Norway rats which had received 2000R of local X-irradiation to the temporarily hypoxic, exteriorized, ileum and jejunum regardless of whether a small bowel adenocarcinoma subsequently developed. The cytotoxic response, which was detectable at two days, was quite evident by day 5 post-irradiation. No evidence of cross-reacting tumor antigens was obtained when similarly processed effector cells from Holtzman rats bearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Further, the spleen need not be irradiated to produce AIRIM, whereas Moroson and Schechter reported that shielding the spleen abolished their effect. Our experiments point to the intestine as a likely target tissue for induiction of AIRIM, and it is of interest that Stevens et al (1978) have reported that irradiation of the exteriorized jejunum and ileum of rats led to the appearance of peripheral lymphocytes cytotoxic to cultured cells of a radiationinduced gut adenocarcinoma. In their experiments, cytotoxic lymphocytes could be detected as early as 2 days after irradiation, increased in numbers for at least 4 wveeks and then persisted for up to a year, a time course quite dissimilar from that of AIRIM.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the spleen need not be irradiated to produce AIRIM, whereas Moroson and Schechter reported that shielding the spleen abolished their effect. Our experiments point to the intestine as a likely target tissue for induiction of AIRIM, and it is of interest that Stevens et al (1978) have reported that irradiation of the exteriorized jejunum and ileum of rats led to the appearance of peripheral lymphocytes cytotoxic to cultured cells of a radiationinduced gut adenocarcinoma. In their experiments, cytotoxic lymphocytes could be detected as early as 2 days after irradiation, increased in numbers for at least 4 wveeks and then persisted for up to a year, a time course quite dissimilar from that of AIRIM.…”
Section: Discussionmentioning
confidence: 99%